The Principal's Strategy in Improving Teacher Performance at SD Negeri 13 Tanah Abang - Rastiana Rastiana; Winda Nopriani; Leny Marlina; Asri Karolina (The Future of Education Journal, 2024)
The principal's role as an educational manager is very important in ensuring that the school he leads has good quality learning. The principal's strategy is one way to improve teacher performance in the learning process. This research is entitled "School Principal's Strategy in Improving Teacher Performance" with the aim of finding out how the principal at SD Negeri 13Tanah Abang implements this strategy. Success in achieving this goal depends on the school principal's ability to develop strategies that are appropriate to existing conditions, in order to improve the quality of learning. The role of an effective school principal will have a positive impact on teacher enthusiasm in carrying out their duties. This research uses a qualitative approach with data collection techniques through observation, interviews and documentation. The data obtained is presented using a descriptive approach, using words or statements from the subjects observed, such as school principals, teachers and students. The results of the research show that the principal's strategy for improving teacher performance, including coaching and monitoring performance, discipline of educational staff, providing motivation and rewards, has been working even though there are several aspects that are not optimal. Teacher performance in terms of preparing learning tools, evaluating learning outcomes, and following up on learning results is classified as good, but the use of methods and media in implementing learning still needs to be improved.